USING DICTATION AS A TESTING DEVICE IN TEACHING LISTENING - Fatma Yuniarti (INOVISH JOURNAL, 2017)
Abstract: The objectives of the research are (1) to know the students response in teaching listening by using dictation (2) to describe how the improvement of students listening skill using dictation as a testing device. The type of this research is Classroom Action Research (CAR). The researcher implements dictation as a testing device in teaching listening within two cycles. Each cycle consists of two meetings. Every cycle consisted of four steps, including planning, acting, observing, and reflecting. The qualitative data were acquired by observation, interview, and field notes. Meanwhile, the quantitative data were collected from the students pre-test and post-test during the implementation of the actions which were analyzed to get the mean scores to be compared and to determine the gain scores. Based on the observation checklist, the students’ response in learning listening became better. The result of the research shows that there are improvements in teaching and learning process. In the pre-test given before the treatment, the mean score is 50.45. After treatment in cycle 1 and conducting post-test 1, the means score is improved to 65.65. Then the researcher gives treatments in cycle 2. In the post-test 2, the mean score improved 79.16. From the explanation above, it can be concluded that using dictation technique in teaching listening could improve students listening skill and the students give positive response.